If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -5y = 4(-1y + -6) + 5(4y + 3) Reorder the terms: 5 + -5y = 4(-6 + -1y) + 5(4y + 3) 5 + -5y = (-6 * 4 + -1y * 4) + 5(4y + 3) 5 + -5y = (-24 + -4y) + 5(4y + 3) Reorder the terms: 5 + -5y = -24 + -4y + 5(3 + 4y) 5 + -5y = -24 + -4y + (3 * 5 + 4y * 5) 5 + -5y = -24 + -4y + (15 + 20y) Reorder the terms: 5 + -5y = -24 + 15 + -4y + 20y Combine like terms: -24 + 15 = -9 5 + -5y = -9 + -4y + 20y Combine like terms: -4y + 20y = 16y 5 + -5y = -9 + 16y Solving 5 + -5y = -9 + 16y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-16y' to each side of the equation. 5 + -5y + -16y = -9 + 16y + -16y Combine like terms: -5y + -16y = -21y 5 + -21y = -9 + 16y + -16y Combine like terms: 16y + -16y = 0 5 + -21y = -9 + 0 5 + -21y = -9 Add '-5' to each side of the equation. 5 + -5 + -21y = -9 + -5 Combine like terms: 5 + -5 = 0 0 + -21y = -9 + -5 -21y = -9 + -5 Combine like terms: -9 + -5 = -14 -21y = -14 Divide each side by '-21'. y = 0.6666666667 Simplifying y = 0.6666666667
| 4x^3-12x^2-40x=0 | | 20x^5/5x^3 | | -9x(-36)=18 | | a^4-4a^2-6= | | 1/3(w+2)=-5 | | jx+by=c | | 12x-3x+14=8+6+9x | | 9y-4=12y-2 | | 864=(1/2)(18*4)(l)+(18*18) | | 3(-4)+3(-6)=-6 | | 1/3(w+2) | | 3=-1+x | | 8/9x-8=y | | -9(0)-7y=63 | | (5x+2)(10x-3)=(2x+3)(x-8) | | 3(n-11)=42 | | n/4-2/3=5/6 | | 4w-5/3=2w+12/4+w/2 | | 2+4(4x-3)= | | -x+1=-4 | | -9-3=33 | | 0.05m=8 | | 3(x-4)=-5(6-x) | | 2x^4-14x^3+12x^2-15=0 | | 15+2p=17 | | -x^7+5x^2-2x^2= | | 2/7(21y+14)-2(4y+6)=0 | | 5x-3=7x+3x | | -24+-24=42 | | 3x+15x-15=-3 | | 9(m-[-5])=108 | | y=3mx-5b |